(untitled) (Revista do LabDGE - UFF, 2023)
The objective of this paper is to identify ways of managing capacity in healthcare settings and apply them to Emergency Care Units. The methodology used is based on three pillars: 1. lexical and content analysis of existing scientific articles in the Scopus database; 2. quantify and qualify the existence of publications by identifying the correlations between authors using VOSviewer; 3. proposed application of capacity management in 50 Emergency Care Units. The results showed that with Capacity Management it is possible to generate activities that add more value to the infrastructure and control service delivery, eliminating queues and bottlenecks in the healthcare environment, thus contributing to effective service through continuous flow in the urgency and emergency of 24 h ECUs.